(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
’Industrial Sickness’ is a broad generalized phrase that puts together two separate ’industrialization’ terms, an economic transition that carries socioeconomic change in its midst, and ’sickness’, a clinical-pathological nomenclature that denotes a deficiency or disorder in the body. Taken together, these two suggest a certain barrier to economic production and focus harmfully on all those associated with an industrial unit that is ill. Indeed, an ailing manufacturing unit affects the social microcosm under which it operates in many respects-owners shareholders are deprived of sufficient returns on their investment workers employees are deprived of daily wages wages giving rise to family tension and indebtedness issues the income of suppliers subcontractors is jeopardised, also causing subsistence issues for them end-product usage.